Role of the Insect Neuroendocrine System in the Response to Cold Stress - Lubawy, Jan; Urbański, Arkadiusz; Colinet, Hervé; Pflüger, Hans-Joachim; Marciniak, Paweł (Frontiers in Physiology, 2020)
Insects are the largest group of animals. They are capable of surviving in virtually all environments from arid deserts to the freezing permafrost of polar regions. This success is due to their great capacity to tolerate a range of environmental stresses, such as low temperatures. Cold/freezing stress affects many physiological processes in insects, causing changes in main metabolic pathways, cellular dehydration, loss of neuromuscular function and imbalance in water and ion homeostasis. The neuroendocrine system and its related signaling mediators, such as neuropeptides and biogenic amines, play central roles in the regulation of the various physiological and behavioral processes of insects and hence can also potentially impact thermal tolerance. In response to cold stress, various chemical signals are released either via direct intercellular contact or systemically. These are signals which regulate osmoregulation - capability peptides, inotocin-like peptides, ion transport peptide, diuretic hormones and calcitonin, substances related to the general response to various stress factors - tachykinin-related peptides or peptides responsible for the mobilization of body reserves. All these processes are potentially important in cold tolerance mechanisms. This mini-review summarizes the current knowledge on the involvement of the neuroendocrine system in the cold stress response and the possible contributions of various signaling molecules in this process.